Presenting features of supraglottic carcinoma of larynx (Bangladesh Journal of Otorhinolaryngology, 2011)
Objectives: To find out the presentation of supraglottic carcinoma of larynx.Methods: Fifty cases of supraglottic carcinoma were selected from the in-patient department of Otolaryngology and Head-Neck surgery of Bangabandhu Sheikh Mujib Medical University and Dhaka Medical College Hospital, Dhaka, during March, 2009 to August, 2009.Results: Among 50 cases in this study male: female ratio 11.5:1 and mean age was 55 years with range 35 years to 80 years. Majority of cases were from the lower socioeconomic group (66%). Regarding habit 94% were smoker, 60% were habituated with chewing betel leaf and betel nuts with or without other ingredient. Only 3 cases (6%) were alcoholic. Most of the cases presented with more than one symptoms and commonest symptoms was change of voice (82%) which was followed by dysphagia (76%), respiratory distress (54%) and neck swelling (42%). 32 (64%) cases had enlarged cervical lymph nodes out of which 27 (84.37%) were homolateral, 4 (12.50%) were bilateral and only 1 (3.12%) was contra-lateral. Vocal cord movement was normal in 23 (46%) cases, impaired in 12 (24%) and fixed in 15 (30%) cases. Most of the cases presented with exophytic lesion 34 (68%) where ulcerative lesion was 16 (32%). (52%) presented with involvement of arytenoid with aryepiglottic folds/vestibule of larynx, 12 cases (24%) had lesion at epiglottis with vestibule/aryepiglottic folds, 8 cases (16%) had lesion at vestibule with false cord, 4 cases (8%) had lesion involving the epiglottis only. Maximum number of patients had T3 lesion (44%) and T2 lesion was 36%. Most of the cases presented at an advanced stage, stage- IV was 42% and stage- III was 36%. Stage- I and stage- II were 6% and 16% respectively. Conclusion: Most common presenting symptoms of supraglottic carcinoma were change of voice, dysphagia and respiratory distress and most of the cases prented in an advanced stage (Stage III and Stage IV). Key words: Supraglottic; personal habit; neck node DOI: 10.3329/bjo.v16i2.6845Bangladesh J Otorhinolaryngol 2010; 16(2): 106-112